PERANCANGAN MEDIA PROMOSI WISATA ALAM ARUNG JERAM BOSAMBA SEBAGAI UPAYA MENINGKATKAN BRAND AWARENESS - Oktarina, Rinda; Bahruddin, Muh; Dewanto, Thomas Hanandry (Jurnal Art Nouveau, 2014)
Nature Bosamba Rafting is one of the sights that have the potential to become one of the sights of the city Bondowoso . Bosamba a nature rafting ( rafting ) as well as to enjoy the natural beauty along the river that served New Sampean . Nature tourism rafting Bosamba has a lot of potential to be developed and promoted . But the promotion is done today is considered less and yet effective. If done promotional strategy to highlight the uniqueness of nature Bosamba rafting , then the public will be more aware and want to come visit Bosamba . The uniqueness which differentiates it from similar tourist rafting tours are relaxed and enjoy the natural beauty in the form of cliffs and waterfalls which are located around the rafting . By uniqueness can be a characteristic that is difficult to imitate by competitors alike. Of the existing problems , then this design is to design a media campaign directed nature rafting Bosamba an effort to increase brand awareness .